PENINGKATAN EFISIENSI PROSES ADMINISTRASI DESA MELALUI IMPLEMENTASI SISTEM MANAJEMEN DOKUMEN TERINTEGRASI - Riduan Siagian; Jumadiah Wardati; Nana Soraya (Jurnal Industri Kreatif dan Inovatif, 2025)
This Community Service activity aims to improve the efficiency of village administration processes through the implementation of an integrated Document Management System (DMS). The main problems faced by partners include long file searches, document duplication, non-standard storage, the risk of archive loss/damage, and undocumented disposition flows. The implemented solutions include process mapping, the development of archiving SOPs, the establishment of document classification structures, the digitization of priority documents, and training on DMS use and access governance. The results of the activity showed improvements in document retrieval times, archive tidiness, and document traceability, along with increased capacity of village officials in standardized document management.